Structural geology and tectonic geomorphology of the Northeastern Cauca-Amagá Valley basin, Northern Andes block : evidence of neotectonics along the Cauca-Romeral fault system (2020)
We disclose new evidence of neotectonic activity associated with the Romeral fault system in the western flank of the Central Cordillera of the Colombian Andes and, provide a geomorphological analysis of a dynamic fluvial system related to this structural setting. This region is populated by several large cities and has been attached to a recent history of natural disasters such as the 1999 Armenia earthquake, therefore the effort to understand relative timing and surface expression of neotectonic events is more than worth. We use an integrated approach of structural geology and tectonic geomorphology to understand the relationship between geomorphic markers and active faults and other controls of landscape evolution such as denudation and fluvial agents. We propose that neotectonics in the study area is caused by triple-point stress within a transpressive kinematic model, that produced compressive and distension stress tensor along the Arma fluvial system and a clockwise motion on the western structural blocks.